A new species of Cnemaspis (Sauria: Gekkonidae) from Sri Lanka - Wickramasinghe, L. J. Mendis (Zootaxa, 2006)
A new species of Cnemaspis, C. ranwellai is described from Gannoruwa in the Central Province of Sri Lanka. This species differs from all other Cnemaspis species by having 12–15 femoral pores and having spine-like tubercles on the body and tail. Males have a distinct yellow colour in the throat area. It is similar to Cnemaspis jerdoni scalepensis Ferguson, 1877, but differs from the former by having spine-like tubercles in the tail, a fewer number of ventral scales at mid ventral region, presence of dorsal tubercles in the mid body area and by having completely different colour patterns in the throat and dorsal neck region.